Peritoneal dialysis-related peritonitis: twenty-seven years of experience in a Colombian medical center (2014)
ABSTRACT: Peritonitis has been the most common complication of continues ambulatory peritoneal dialysis (CAPD) since it was first implemented, and it remains the leading cause of treatment failure and transfer to other renal replacement therapies. This study presents a Colombian series with a total of 2469 episodes of peritonitis in 914 patients from a cohort of 1,497 patients on PD, who were followed for almost three decades at a single center. This is the largest Latin American series of patients with PD-related peritonitis. Objective: To describe the CAPD-related peritonitis in a cohort of patients followed for 27 years at a single center, and compare the results with those observed elsewhere in the world. Study Design: Prospective study of incident patients on CAPD from march 1981 to December 2008. Results: In our center, the rate of peritonitis has been steady between 0.8 and 0.9 since 1981 and no signiicant changes have been noticed in the 27 years of follow up. The rate remains similar to that described nowadays by other large dialysis centers in the world, which have reported signiicant improvements in recent decades. No signiicant differences were found in the isolates of gram-positive and gram-negative microorganisms or fungi with respect to those reported by other large series, or in the frequency of culture-negative peritonitis. Conclusion: This study presents the largest Latin American series of patients with CAPD-related peritonitis with a total of 2,469 patients. In this study, the rate of CAPD related peritonitis remained almost the same during the three decades of observation despite having used three different CAPD systems. Our hypothesis is that the socio-economic conditions of the patients admitted for peritoneal dialysis inluences the rate of peritonitis.